Hands-on enterprise automation on Linux : efficiently perform large-scale Linux infrastructure automation with Ansible - Freeman, James (Packt Publishing, 2020)
Anyone responsible for a Linux server infrastructure will be able to improve the reliability of their environment and efficiency of their operations with this book, ""Hands-on Enterprise Automation on Linux"". This, in turn, will help to reduce operating costs and the stresses and workload placed on those responsible for the environment